Cardiopulmonary exercise testing as a guideline indicator for mitral valve intervention. (25th November 2020) - Afoke, J; Kanaganayagam, G.S; Casula, R; Bruno, V.D; Howard, L; Gibbs, J.S.R; Punjabi, P
Abstract: Background: Primary mitral regurgitation (MR) is one of the most common heart valvular pathologies. However, optimum timing of surgery remains controversial. Purpose: To describe changes in cardiopulmonary exercise testing (CPET) parameters after surgery for severe primary MR. Methods: In a single centre prospective study, patients undergoing surgery under current ESC guidelines for severe primary MR underwent assessment with transthoracic echocardiogram, CPET, cardiac MRI and quality of life questionnaire pre-operatively and at six months after surgery. The primary outcome was a per protocol analysis of impaired post-operative functional capacity (defined as post-operative left ventricular ejection fraction on transthoracic echocardiogram <50% and/or post-operative percentage predicted peak VO2 ≤84%). Results: 43 of the 50 patients recruited between February 2017 and October 2018 were included in the per protocol analysis. Thirty five patients (72.9%) had impaired post-operative functional capacity. In the overall cohort (n=43), there was a significant fall post-operatively in percentage predicted peak VO2 (ppVO2) (81.8±15.7% vs. 76.2±16.2%, p<0.01) and anaerobic threshold (AT) (48.0±11.1% vs. 44.3±10.1%, p=0.01). In patients with a class I indication for surgery (n=30), there was no significant change post-operatively in ppVO2 (79.6±15.7% vs. 75.6±16.7%, p=0.09) or AT (49.9±11.4% vs. 46.4±10.2%, p-0.09). However, in patients with a class II indication for surgery (n=13), there was a significant change post-operatively in ppVO2 (86.9±15.1% vs. 77.4±15.9%, p<0.01), but not in AT (43.5±9.6% vs. 39.5±8.3%, p=0.16). In the multivariable analysis, pre-operative left ventricular ejection fraction ≤60% (hazard ratio, 1.69; 95% confidence interval, 1.56 to 480.1, p=0.04) and pre-operative percentage predicted peak VO2 ≤84% (hazard ratio, 1.22; 95% confidence interval, 2.13 to 107.1, p<0.01) were independent predictors for impaired post-operative functional capacity. Conclusions: Pre-operative percentage predicted peak VO2 ≤84% is an independent predictor of impaired post-operative functional capacity. Subject to a confirmatory study, this may help to refine current ESC guidelines for intervention for severe primary MR. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Rosetrees Trust and Friends of Hammersmith Hospital